Kidney Transplantation in Patients With Alport Syndrome - Mojahedi, Mohammad Javad; Hekmat, Reza; Ahmadnia, Hassan (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate the results of kidney transplantation in patients with Alport syndrome. Materials and Methods: A total of 15 patients with Alport syndrome underwent kidney transplantation and the result of their transplantation was compared with the results in patients without Alport Syndrome. Rejection episodes and the presence of antiglomerular basement membrane (anti-GBM) nephritis were assessed in these patients. Results: Fifteen patients with Alport syndrome were compared with a control group including 212 kidney allograft recipients. One patient with Alport syndrome (6.7%) and 30 controls (14.2%) experienced delayed graft function. Renal artery thrombosis was reported in 1 patient (6.7%) with Alport syndrome and 10 (4.7%) in the control group, which led to nephrectomy in all cases. Acute rejection was confirmed in 2 patients (13.3%) by kidney biopsy and classic treatment yielded relative response. However, they lost their grafts 35 and 44 months after the transplantation. On pathologic examination, no specific finding of anti-GBM nephritis was found. In the control group, 43 cases of acute rejection (20.3%) were reported and 12 patients (5.7%) returned to dialysis. The 1-, 3-, and 5-year graft survival rates were 100%, 92%, and 84% in the patients with Alport syndrome, which was not different from those in the control group (P = .53). Conclusion: In spite of the risk of anti-GBM nephritis in the patients with Alport Syndrome, it seems that kidney transplantation can yield favorable results and anti-GBM nephritis is not a common etiology of rejection.